2015
DOI: 10.1111/jfpp.12622
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and In vitro Antioxidant Activity of a Polysaccharide from C ordyceps sobolifera

Abstract: The characteristics and antioxidant activities of Cordyceps sobolifera polysaccharide (CSP) were investigated. Results from high-performance gel filtration chromatography showed that the average molecular weight of CSP was 1.53 × 10 4 kDa, while this polysaccharide was mainly composed of mannose, glucose and galactose in the molar ratio of 1.7:8.9:1 as determined by high-performance liquid chromatography after pre-column derivatization with 1-phenyl-3-methyl-5-pyrazolone. Fourier-transform infrared spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In contrast, intracellular PSs (IPSs) from mycelia contain various polyglucans as well as Glc [ 20 , 21 ]. Compositions of other Cordyceps species were generally similar to those of C. sinensis [ 22 , 23 , 24 , 25 ], although some other monosaccharides, such as Rha, Xyl, Fru and Ara, were present in C. cicadae and C. kyushuensis [ 26 , 27 ]. In Morchella esculenta , another well-known ascomycete, the PSs contain four or more monosaccharides [ 28 , 29 , 30 ].…”
Section: Monosaccharide Composition Combinations and Bioactivitimentioning
confidence: 99%
“…In contrast, intracellular PSs (IPSs) from mycelia contain various polyglucans as well as Glc [ 20 , 21 ]. Compositions of other Cordyceps species were generally similar to those of C. sinensis [ 22 , 23 , 24 , 25 ], although some other monosaccharides, such as Rha, Xyl, Fru and Ara, were present in C. cicadae and C. kyushuensis [ 26 , 27 ]. In Morchella esculenta , another well-known ascomycete, the PSs contain four or more monosaccharides [ 28 , 29 , 30 ].…”
Section: Monosaccharide Composition Combinations and Bioactivitimentioning
confidence: 99%
“…Recent studies have found that C. cicadae contains metabolites with important pharmacological functions. Examples of these include the carbon compound mannitol, which is a diuretic, exhibits antifree-radical activity, and improves cerebral microcirculation and blood flow (Lin et al, 2016;Zhang et al, 2019); polysaccharides, which are also essential carbon compounds, have antioxidant properties and play a role in treating diabetes and improving immune regulation (Lu et al, 2016;Zhang et al, 2018;Wang et al, 2019); adenosine, a nucleoside with anti-inflammatory, neuroprotective and anti-convulsive properties, which has been shown to improve cell viability and prevent and treat neurodegenerative diseases (Latini and Pedata, 2001;Nakav et al, 2008;Olatunji et al, 2016b); and cordycepin, another nucleoside with anti-cancer, immune regulation, and antioxidant functions (Olatunji et al, 2016a;Zhang et al, 2019). Owing to its use as a medicine and tonic, wild C. cicadae has been harvested at unsustainable levels, resulting in a significant population reduction in its natural habitats (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The PS-T80 average molecular weight is lower than isolated PS from the same species introduced by Lu et al (2016), which is 1.53 × 10 4 kDa. 11 Furthermore, the obtained value is higher than those extracted from Cordyceps sinensis ( C. sinensis ) and Cordyceps militaris ( C. militaris ), ranging from 12.9 to 460 kDa. 30 33 …”
Section: Resultsmentioning
confidence: 79%